2014
DOI: 10.1002/pola.27504
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of particle morphology during the synthesis of hybrid acrylic/CeO2 nanocomposites by miniemulsion polymerization

Abstract: The evolution of the morphology of an acrylic/CeO2 hybrid latex synthesized by a two step seeded semibatch emulsion polymerization process was investigated. The seed was produced by batch miniemulsion polymerization and in the second step a neat monomer preemulsion was fed to the seed to increase the solids content and encapsulate the inorganic material. The morphology of the hybrid miniemulsion droplets, the seed and the final latex was analyzed by TEM. The morphologies achieved could be explained by theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In this regard, it is worth mentioning that in miniemulsion polymerization θ wos may strongly change during the process because both γ ow and γ os may be very different for monomer and polymer. Proof of this change is provided by the evolution of the particle morphology observed in the miniemulsion polymerization of MMA/BA droplets containing cerium oxide . This change may be the reason for the strong increase in particle size observed in the first moments of the Pickering miniemulsion polymerization of vinyl acetate and Veova10 …”
Section: Polymer–inorganic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it is worth mentioning that in miniemulsion polymerization θ wos may strongly change during the process because both γ ow and γ os may be very different for monomer and polymer. Proof of this change is provided by the evolution of the particle morphology observed in the miniemulsion polymerization of MMA/BA droplets containing cerium oxide . This change may be the reason for the strong increase in particle size observed in the first moments of the Pickering miniemulsion polymerization of vinyl acetate and Veova10 …”
Section: Polymer–inorganic Systemsmentioning
confidence: 99%
“…Furthermore, the morphology map also accounts for the effect of the monomer system on particle morphology observed in an attempt to encapsulate nickel nanoparticles in polystyrene and poly(methyl methacrylate) . The predicted location of CeO 2 particles on the surface of polyacrylate polymer particles could be, however, modified to encapsulation of inorganic particles, by a second step semibatch polymerization of the acrylic monomers …”
Section: Polymer–inorganic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology observed is completely different, as the nanoparticles tend to aggregate, which means that the incompatibility between the newly formed polymer and the surface of the CeO 2 nanoparticles has increased or that IP has become higher. This change in the morphology with the presence of polymer is observed too when the acrylic/CeO 2 hybrid miniemulsion is prepared adding a polymer in order to increase the stability of the miniemulsion [66]. At 8% of conversion, the difference becomes more evident, the nanoparticles are more aggregated and they tend to move towards the border of the polymer particles.…”
Section: Evolution Of Particle Morphology During the Synthesis Of Acrmentioning
confidence: 95%
“…[12] The performance of the composite latex particles is directly affected by their morphology and due to its practical importance, particle morphology has received a considerable attention in the literature. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Several authors reported theoretical approaches aimed at predicting the particle morphology, but most of the methods are based on two limiting assumptions: either the polymer chains do not move from the point that they are formed [25,[27][28][29][30][31] or the equilibrium morphology is attained instantaneously. [11,[32][33][34][35][36][37][38][39][40] There are only few works in the literature that take into account all relevant kinetic and thermodynamic effects.…”
Section: Introductionmentioning
confidence: 99%